Nucleobindin 1 (NUCB1) is a Golgi-resident marker of neurons. (9th February 2016) - Tulke, S.; Williams, P.; Hellysaz, A.; Ilegems, E.; Wendel, M.; Broberger, C.
Highlights: First mapping of the Ca 2+ -binding protein nucleobindin 1 (NUCB1) in the brain. NUCB1 is a novel pan neuronal marker throughout the nervous system. NUCB1 is co-expressed with NUCB2/nesfatin in a subset of hypothalamic neurons. NUCB1 is consistently associated with the Golgi apparatus. Findings indicate a broader role for nucleobindin proteins in the nervous system. Abstract: Nucleobindin 1 (NUCB1; also known as CALNUC or NUC) is a putative DNA- and calcium-binding protein and exhibits significant structural homology with the protein nucleobindin 2 (NUCB2; also known as nesfatin). While NUCB2 has been mapped in detail in the brain and implicated in the hypothalamic control of energy metabolism, no study has to date addressed the presence of NUCB1 in the central nervous system. Here we have explored the expression and distribution of NUCB1 in the rat brain and spinal cord, using RT-PCR, immunofluorescence and in situ hybridization. NUCB1 mRNA and protein was found to be present in all brain regions, extending to the spinal cord and dorsal root ganglia. Double-staining for NUCB1 and NeuN, glial fibrillary acidic protein and myelin basic protein revealed that NUCB1 is exclusively found in neurons, and not in glial or ependymal cells. Notably, NUCB1-immunoreactivity was observed in all neurons examined, making no distinction between previously identified glutamatergic and GABAergic populations, including those that are known not to stain for NeuN. This included the markedly more restricted population of NUCB2-expressing neurons in the brain. The protein was detected in cell somata and proximal dendrites, but not in axons or terminal structures. Further examination of the subcellular distribution of NUCB1 using organelle-specific markers revealed its consistent presence in the Golgi apparatus. These findings identify NUCB1 as a novel pan-neuronal marker. Along with the recent demonstration of broad expression of the protein in endocrine cells, the present results suggest that NUCB1 may play a role in spatiotemporal calcium handling in signaling cells.